Faktor Determinan yang Berhubungan dengan Kejadian Stunting Pada Balita Usia 1–3 Tahun di Wilayah Pesisir Kabupaten Brebes - Ikhtiarti, Wulandari; Rahfiludin, M. Zen; Nughraheni, S. A. (Jurnal Ilmiah Mahasiswa, 2020)
Title : Determinant of Stunting Incidence on Infant (1-3 Years old) at Coastal of Brebes DistrictBackground : Stunting is a public health nutrition problems which indicate condition of growth failure in children under five. Coastal areas need to be considered both in management of health life and environmental sanitation. Prevalence of stunting in Brebes regency is 32.7% which is still higher than national figure. This study aims to analyze the risk factors for stunting in the coastal areas of Brebes Regency. Methods : This is an observational study with a case control design. Samples were taken as many as 30 in each case and control group. Data were analyzed to determine stunting risk factors in coastal areas. Result : The results showed that there were lack of environmental sanitation (p 0.001; OR 8.00: 95% CI 2,475 - 25,860), people suffering from infectious diseases (p 0.001; OR 17.875; 95% CI 4.738 - 67.434), lack of caregiver knowledge (p 0.032; OR 0.304 95% CI 0,100 - 0,922), lack of energy intake (p 0,008; OR 4,297; 95% CI 1,413 - 13,068), low economic status (p 0,136; OR 2,500; 95% CI 0,735 - 8,502), lack of energy intake (p 0.095; OR 3.273; 95% CI 0.774 - 13.832). Conclusion : Poor environmental sanitation, infectious diseases, lack of caregiver knowledge and lack of energy intake are risk factors for stunting while low economic status and lack of protein are not risk factors for stunting.